1995
DOI: 10.1016/s1078-5884(05)80220-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive aortoiliac assessment

Abstract: Pressure measurements remain the gold standard for aortoiliac examination, arteriography providing only morphological information. The limitations of femoral pulse palpation should be appreciated. Although MRA was faster, Duplex examination proved slightly more sensitive to stenoses. At present, colour Duplex provides the best non-invasive assessment of aortoiliac disease and could prevent unnecessary arteriograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 10 publications
0
24
0
1
Order By: Relevance
“…Duplex ultrasound also has broad clinical utility for evaluation of aneurysms, arterial dissection, popliteal artery entrapment syndrome, evaluation of lymphoceles, and assessment of soft tissue masses in individuals with vascular disease. Although duplex ultrasound includes images, either in black and white or color format, the primary clinically relevant information derived from duplex studies has been validated from analysis of the velocity of blood flow (201)(202)(203)(204)(205)(206)(207)(208)(209). Quantitative criteria used to diagnose stenoses are based on peak systolic velocity and peak systolic velocity ratios within or beyond the stenosis compared with the adjacent upstream segment, the presence or absence of turbulence, and preservation of pulsatility.…”
Section: Treadmill Exercisementioning
confidence: 99%
“…Duplex ultrasound also has broad clinical utility for evaluation of aneurysms, arterial dissection, popliteal artery entrapment syndrome, evaluation of lymphoceles, and assessment of soft tissue masses in individuals with vascular disease. Although duplex ultrasound includes images, either in black and white or color format, the primary clinically relevant information derived from duplex studies has been validated from analysis of the velocity of blood flow (201)(202)(203)(204)(205)(206)(207)(208)(209). Quantitative criteria used to diagnose stenoses are based on peak systolic velocity and peak systolic velocity ratios within or beyond the stenosis compared with the adjacent upstream segment, the presence or absence of turbulence, and preservation of pulsatility.…”
Section: Treadmill Exercisementioning
confidence: 99%
“…29,30,32,40,41,54,57,60,61 In addition, 46 studies that did not meet the inclusion criteria for the review of diagnostic accuracy reported results relating to adverse events. 78,80, …”
Section: Adverse Eventsmentioning
confidence: 99%
“…One study evaluated 2D PC MRA, 66 11 evaluated 2D TOF MRA, 22,27,29,32,40,41,53,55,64,69,74 and 14 evaluated CE MRA. 9,28,36,46,49,51,53,61,65,67,68,70,73,76 There were no studies providing results for the assessment of 3D TOF MRA.…”
Section: Mramentioning
confidence: 99%
See 2 more Smart Citations